Searching for Support and Community: Experiences in a Gay Men’s Psyhcoeducational Group - Frank, Blye W.; Fisher, Art (Canadian Journal of Counselling and Psychotherapy, 2007)
Support groups are a powerful tool that can assist gay men in dealing with isolation from other gay men, a lack of information about themselves and others as gay men, and the fear either of being identified or of self-identifying as gay. In this article, ten gay men speak about their experiences in a support/psychoeducational group.